DESCRIPCION DE UN PARAMONOSTOMUM TREMATODA NOTOCOTYLIDAE ENCONTRADO EN LOS PATOS SILVESTRES DEL LAGO DE TEXCOCO V - CABALLERO Y C, EDUARDO (Museo de Historia Natural, Tuxtla Gutiérrez, Chiapas, MEX, 1943)
The author creates a new sub-family CHOANOPHORINAE in the family Pronocephalidae, for the new genus CHOANOPHORUS and species C rovirosai, and describes, also, Octangioides tlacotalpensis , found in the intestine of a fresh-water turtle, Dermatemys mawii
ANS INST BIOL
Keywords: DESCRIPCION, PARAMONOSTOMUM, TREMATODA: NOTO COTYLIDAE ENCONTRADO, PATOS SILVESTRES, LAGO DE TEXCOCO; CIENCIAS DE LA VIDA; BIOLOGIA ANIMAL; PARASITOLOGIA ANIMAL